morphoHeart: A quantitative tool for integrated 3D morphometric analyses of heart and ECM during embryonic development. - Juliana Sánchez-Posada; Christopher J Derrick; Emily S Noël (PLoS Biology)
Heart development involves the complex structural remodelling of a linear heart tube into an asymmetrically looped and ballooned organ. Previous studies have associated regional expansion of extracellular matrix (ECM) space with tissue morphogenesis during development. We have developed morphoHeart, a 3D tissue segmentation and morphometry software with a user-friendly graphical interface (GUI) that delivers the first integrated 3D visualisation and multiparametric analysis of both heart and ECM morphology in live embryos. morphoHeart reveals that the ECM undergoes regional dynamic expansion and reduction during cardiac development, concomitant with chamber-specific morphological maturation. We use morphoHeart to demonstrate that regionalised ECM expansion driven by the ECM crosslinker Hapln1a promotes atrial lumen expansion during heart development. Finally, morphoHeart's GUI expands its use beyond that of cardiac tissue, allowing its segmentation and morphometric analysis tools to be applied to z-stack images of any fluorescently labelled tissue.